Three-observer Bell inequality violation on a two-qubit entangled state. (21st March 2017) - Schiavon, Matteo; Calderaro, Luca; Pittaluga, Mirko; Vallone, Giuseppe; Villoresi, Paolo
Abstract: Bipartite Bell inequalities can simultaneously be violated by two different pairs of observers when weak measurements and signalling is employed. Here, we experimentally demonstrate the violation of two simultaneous CHSH inequalities by exploiting a two-photon polarisation maximally entangled state. Our results demonstrate that large double violation is experimentally achievable. Our demonstration may have impact for Quantum Key Distribution or certification of Quantum Random Number generators based on weak measurements.